Identifying Public Value of Zakat Management Organizations: A Review of Muzaki's Perception - Ansoriyah, Faizatul; Kushandajani; Hartuti Purnaweni; Retno Sunu Astuti; Son Haji (DINIKA : Academic Journal of Islamic Studies, 2023)
Zakat gain in Indonesia as the largest Muslim country in the world has not been compatible to its potential. The issuance of Law Number 23 of 2011 about Zakat management is the manifestation of Government’s attention to an attempt of maximizing zakat management. This study aims to analyze the public value of Zakat Managing Organization (Indonesian: Organisasi Pengelola Zakat or OPZ) viewed from muzaki’s perspective. The research method used was mix methods by analyzing the vision and mission of zakat managing organization and interviewing the zakat institution organizer, and using face-to-face questionnaire distributed to muzakis. The result of the research shows that there are some values identified for zakat managing organization: trustability (amanah), accountability, transparency, and synergy. Trust or trustability is intrinsic value, while accountability, transparency, and synergy are instrumental values.  The identified indicator of both intrinsic and instrumental values can be the basis for OPZ to consider muzakis’ need to maximize zakat management.